Educational creative use and reuse of digital cultural heritage data for cypriot UNESCO monuments - Ioannides, Marinos; Chatzigrigoriou, Pavlos; Bokolas, Vassilis; Nikolakopoulou, Vasiliki; Athanasiou, Vasilis; Papageorgiou, Eirini; Leventis, Georgios; Sovis, Christian (My University, 2016)
Nowadays, there is a rising demand of reusing the constantly enriched information from heritage digitalization in different ways. One of the objectives of the EU Europeana Space project is the development of a holistic approach for educating people (grown-ups and kids) on Monuments that are listed at UNESCO world heritage list, in Cyprus. The proposed model action is based on the cross cultural approach which, at the same time, responds to the contemporary pedagogical and methodological directions. The system uses innovative digital heritage resources to help the user learn about the different phases of the monument, the history, the architectural value and the conservation stage. The result is a responsive educational platform, where every Monument is a different course and every course is addressed to different age groups. Moreover, part of our future work is the evaluation of the platform by particular groups of our target users.
Keywords: 3D models; CH data reuse; Cross-cultural; Digital heritage; Education